GKJ-KG Konsep Diri Majelis dan Idealisme Moral dalam Kepemimpinan Kristen-Jawa: Kajian Sosiologi Agama - Adhitya Chris Nugroho; Suwarto Adi; Agus Supratikno (Sekolah Tinggi Teologi Tawangmangu, 2026)
Church leadership within local cultural contexts represents an intersection between theological values and social constructions that shape the practice of faith. In the Javaness tradition, leadership is inseparable from cultural ethics that emphasize harmony, social balance, and refined relational conduct. This study aims to analyze the self-concept of church elders and moral idealism in Javanese-Christian leadership at GKJ Kotagede Yogyakarta, particularly in relation to the low level of congregational participation in church ministry. This research employs a qualitative approach using an ethnographic method to explore subjective experiences, symbolic meanings, and social practices in the relationship between church leaders and congregants. The findings indicate that leadership at GKJ Kotagede is shaped by a dialectic between Christian theology of service and Javanese ethical values that are paternalistic and subtle in nature. This construction positions church elders as the center of moral and spiritual authority, leading congregants to perceive themselves primarily as recipients rather than active subjects of ministry. Consequently, this hierarchical symbolic relationship contributes to the low level of congregational participation. This study recommends the development of a more participatory, dialogical, and emancipatory model of church leadership while remaining rooted in Christian theological values and Javanese cultural traditions. AbstrakKepemimpinan gereja dalam konteks budaya lokal merupakan ruang perjumpaan antara nilai-nilai teologis dan konstruksi sosial yang membentuk praktik hidup beriman. Dalam tradisi Jawa, kepemimpinan tidak dapat dilepaskan dari etika budaya yang menekankan harmoni, keselarasan, dan relasi sosial yang halus. Penelitian ini bertujuan menganalisis konsep diri majelis dan idealisme moral dalam kepemimpinan Kristen-Jawa di GKJ Kotagede Yogyakarta, khususnya kaitannya dengan rendahnya partisipasi jemaat dalam pelayanan kemajelisan. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi untuk memahami pengalaman subjektif, makna simbolik, dan praktik sosial dalam relasi antara majelis dan jemaat. Hasil penelitian menunjukkan bahwa kepemimpinan di GKJ Kotagede dibentuk oleh dialektika antara teologi pelayanan Kristen dan etika budaya Jawa yang bersifat paternalistik dan halus. Konstruksi ini melahirkan figur majelis sebagai pusat otoritas moral dan spiritual, sehingga jemaat cenderung memposisikan diri sebagai penerima pelayanan, bukan sebagai subjek aktif. Akibatnya, relasi simbolik yang hierarkis ini berkontribusi pada rendahnya partisipasi jemaat. Penelitian ini merekomendasikan pengembangan model kepemimpinan gereja yang lebih partisipatoris, dialogis, dan emansipatoris tanpa melepaskan akar teologis dan kultural Jawa.